IRONY DESCRIBING ABOUT ADULTHOOD ANDCHILDHOODIN EMILY BRONTE'S MILD THE MIST UPON THE HILLS - Osiie Ardiles (Universitas Katolik Widya Mandala Surabaya, 2018)
This research aimed to discuss the irony describing childhood and adulthood in Emily Bronteâ€™s â€œMild the Mist Upon the Hillsâ€. This research also had a purpose that is to explain the situational irony related to childhood and adulthood in the poem. The theories that were used in this research were the theory of figure of speech and irony. The approaches that were used in this research were formalistic approach and structural approach. Moreover, descriptive method and library research were used to help the writer to find some data needed.This research figured out some situational ironical statements dealing with the speakerâ€™s childhood and adulthood. In this poem, the speaker tried to reveal some ironical situation that she faced in her entire life. How she picturized the future in her childhood was so great, but after some situation, there were some problems that she might face. However, she still could not have solved it yet. Then, it inspired her to write this poem, because she wanted to express what she felt about her ironical situation.